The Liturgical Books the Metropolitante of Karlovci in XIX Century - Николић, Петар (Sabornost - The Theological Year-book, 2016)
The paper presents a short overview of the liturgical books that were used in the Metropolitante of Karlovci in the nineteenth century. It is known that the first liturgical books were brought from Russia and Ukraine, which are translated by us or reprinted. We have found significant resources to research the liturgical books, chronologically displaying part of print publications in the area Metropolitante of Karlovac and beyond. As a special segment the problems of their reprints are solved, and the reasons were both religious and political.